Effects of low pH and high TA-N on performance of turbot (Psetta maxima) in recirculating aquaculture systems - Mota, Vasco (2011)
Dissertação de mest., Aquacultura e Pescas, Faculdade de Ciências do Mar e do Ambiente, Universidade do Algarve, 2009